A new species of the genus Microgecko Nikolsky, 1907 (Sauria: Gekkonidae) from the southern Zagros Mountains, Iran - Gholamifard, Ali; Rastegar-Pouyani, Nasrullah; Rastegar-Pouyani, Eskandar (Zootaxa, 2019)
The dwarf geckos of the genus Microgecko Nikolsky, 1907 comprise five recognized species, ranging from western Iran to northwestern India. Iran harbors four species of the genus Microgecko. Until now, all populations of the genus Microgecko with a single pair of the postmental shields (as a key diagnostic character) were assigned to M. helenae. Here, based on significant differences in scalation characters, distinct coloration, and ecological peculiarities of habitat as well as support of our present molecular study we distinguish and describe a new species, Microgecko varaviensis sp. nov. within the M. helenae complex, from the southern regions of the Zagros Mountains in Fars Province, southern Iran. Detailed information and an updated identification key for the genus Microgecko are also presented.